Predictors of complications when transferring postoperative cardiac patients from the intensive care unit - K. V. Paromov; M. Yu. Kirov (Патология кровообращения и кардиохирургия, 2017)
Aim. Emphasis in the study was placed on the evaluation of predictors of complications when transferring postoperative cardiac patients from the intensive care unit (ICU). Methods. 60 patients after cardiac surgery were included into this prospective observational study, with 41 of them undergoing off-pump coronary artery bypass grafting (CABG). Before the transfer from ICU, echocardiographical criteria of their systolic and diastolic dysfunction, parameters of oxygenation, hemodynamic and metabolism status, as well as postoperative complications and duration of hospitalization were evaluated. Results. Preoperatively, the patients had a moderate degree of heart failure and preserved ejection fraction. Those patients who had undergone valvular and combined procedures using cardiopulmonary bypass had higher Euroscore II values, more severe heart failure, prolonged duration of surgery, respiratory support and hospitalization in ICU and in hospital. The echocardiographical criteria of diastolic dysfunction before transfer from ICU were recorded in 14-77% patients. Despite a normal range of blood pressure, the systolic function of the left ventricle and preload (left atrial pressure), oxygenation and metabolic status, venous to arterial carbon dioxide difference (Pv-aCO2) and left ventricle performance index (Tei) exceeded the normal values before transfer from ICU. The correlation analysis revealed a relationship between duration of ICU and hospital stay and the criteria of heart failure severity (left atrial pressure [rho = 0.27, 95% CI 0.02–0.48, p = 0.04]) and left ventricle dysfunction (e’ [rho = 0.41, 95% CI 0.17–0.59, p<0.01]) before the transfer. The increase in fluid balance during ICU stay after off-pump coronary artery bypass surgery tended to result in a complicated postoperative period (AUC = 0.73, p = 0.02) and a higher risk of atrial fibrillation. Conclusion. The impairment of the left ventricle diastolic function before transferring from ICU correlates with the duration of hospitalization. A positive fluid balance during ICU period after off-pump surgery might bring about postoperative complications and atrial fibrillation, thus predicting their onset. Received 5 April 2017. Revised 10 August 2017. Accepted 15 August 2017. Funding: The study did not have sponsorship. Conflict of interest: The authors declare no conflict of interest. Acknowledgement The authors express their gratitude for patience and support during the study to the staff of Cardiac Surgery Department and Resuscitation Department.